Περιβαλλοντικές επιδράσεις SO2 / ατμοσφαιρική διάβρωση Zn - Καραχάλιου, Tιμολέων (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
In the current thesis the rate of atmospheric corrosion, , of the zinc surface, in the area of Basilicos in Cyprus, after the first exposure time in air as a function of the amount of dry deposition of SO2 and chlorides, temperature and relative humidity according to the ISO 9223: 2012 as well as of linear polarization measurements. The corrosion rate of a sample is also calculated by the linear polarization resistance method in laboratory scale. Based on the ISO 2010, the average annual corrosion rate is calculated 0.12 micron/year, while in 2015 the corrosion rate decreases to 0.095534 microns/year. The variation of the relative humidity does not significantly affect the rate of corrosion. This may attributed to the fact that the relative humidity does not vary significantly during the year. Based on the experimental results, the corrosion rate was calculated 0.20613 mm/year. This difference may be is due to environmental factors that have not been taken into account during laboratory measurements. Generally atmospheric corrosion of zinc is accelerated by the depositing chlorides and other simultaneously depositing gaseous pollutants, such as sulfur dioxide (SO2). Also humidity plays an important role, but in the early stages of corrosion. The deposition of chloride and sulfur dioxide alter the corrosion of zinc surface by altering the value of pH. In the literature various mechanisms have been proposed for the zinc corrosion in presence of SO2 and NaCl, but further study is necessary.
Keywords: Basilicos; Cyprus; Corrosion rate; Sulfur dioxide; Atmospheric corrosion; Βασιλικός; Κύπρος; Ρυθμός διάβρωσης; Διοξείδιο του θείου; Ατμοσφαιρικής διάβρωση